Energy Management Strategy for Vehicle-to-Grid Technology Integration with Energy Sources: Mini review - Alsharif, Abdulgader; Tan, Chee Wei; Ayop, Razman; Ali Ahmed, Abdussalam Ali; Alanssari, Ahmed; Khaleel, Mohamed Mohamed (African Journal of Advanced Pure and Applied Sciences, 2022)
Energy Management Strategies (EMSs) are used to monitor and control flown power in micro-grid systems. Choosing proper control management can cause unbalance in the power system. This paper presented the used sources to generate electricity in order to feed electric appliances in either or combined forms as renewable and non-renewable energy sources charge and discharge Electric Vehicles (EV) in form of Vehicle-to-Grid (V2G) technology. The classifications of RESs, EVs, and the EMSs were discussed along with their sub-classifications. The considered objectives for energy sources are cost, reliability, and renewability in order to obtain a cost-effective system, low power losses, and a renewable hybrid system. This short communication review is expected to be the best guide for researchers and students who working in the same field